2020
DOI: 10.1044/2020_persp-20-00128
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Children With Speech Sound Disorders During COVID-19 Restrictions: Technological Solutions

Abstract: Purpose “Children are the hidden victims of the COVID-19 pandemic” (United Nations Children's Fund, 2020). Timely and effective speech intervention is important to reduce the impact on children's school achievement, ability to make friends, mental health, future life opportunities, and government resources. Prior to the coronavirus disease (COVID-19) pandemic, many Australian children did not receive sufficient speech-language pathology (SLP) services due to long waiting lists in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the area of language development, in which therapy for phonological skills necessarily requires face-to-face contact, telepractice has proved truly innovative. The benefits of timely and effective telepracticebased intervention during the SARS-CoV2 emergency are especially valuable when the patients also suffer from associated neurodevelopmental disorders (McLeod et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the area of language development, in which therapy for phonological skills necessarily requires face-to-face contact, telepractice has proved truly innovative. The benefits of timely and effective telepracticebased intervention during the SARS-CoV2 emergency are especially valuable when the patients also suffer from associated neurodevelopmental disorders (McLeod et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, children with neurodevelopmental disorders and intellectual disabilities, who had received in-person services before the pandemic, experienced a disruption of care (Bhatia, 2020). Specifically, the literature showed that young children receiving speech and language services experienced a suspension of services and faced many challenges transitioning from in-person to virtual/telehealth support (McLeod, Ballard, Ahmed, McGill, & Brown, 2020). However, because of the need for continuing care despite pandemic conditions, telehealth has become the most viable and effective option for children to receive mental health and developmental services.…”
Section: Impact Of the Pandemicmentioning
confidence: 99%
“…Not much information about the design or development of technology is explicitly stated in the ASHA scope of practice, but the need for these mobile applications and digital experiences was, potentially, even more evident with the onset of the COVID‐19 pandemic (McLeod et al., 2020). The transition from in‐person therapy to teletherapy pushed and demanded practicing clinicians to utilise digital technologies that were appropriate for the clients to continue to meet their goals (Akamoglu et al, 2018; Albudoor & Peña, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps have been defined as computer programs or software applications designed to run on a mobile device (e.g., phone, tablet). Many researchers have reported that SLPs have stated effective use of iPad‐based therapy (iTherapy) for speech and language intervention (Benedon, 2018; Cohen et al., 2017; McLeod et al., 2020) with clients who present various disorders (e.g., autism spectrum (ASD), cerebral palsy, Down syndrome). The majority of the research shows that the use of mobile apps occurs mostly in schools compared to other settings (e.g., hospitals, homes) (Cespedes‐Simangas et al., 2021; Cohen et al., 2017).…”
Section: Introductionmentioning
confidence: 99%